Educational Experts’ Lived Experiences of the Virtual Education Networks for Students of Secondary Schools in Selected Countries (Iran, Iraq, Lebanon, and Syria) - Oday Khalid Lazim AL-Tameemi; Mohammad Ali Nadi; Raed Rasim Younus Aljbara; Zahra Yazdani (Interdisciplinary Journal of Virtual Learning in Medical Sciences, 2024)
Background: Virtual education has provided higher-quality teaching and learning. The current study examines secondary school education experts’ lived experiences and the impact of virtual education networks on students’ scientific, personality, cultural, and religious concepts.Methods: This is a qualitative study using a phenomenological method. All educational experts in the selected countries were interviewed in 2022, and 24 were selected using purposeful and snowball sampling. The data were collected through semi-structured interviews and analyzed using the Colaizzi method. Finally, the validity and reliability of the tool were assessed.Results: A total of 21 components were created from 131 open codes. The scientific concepts included more prosperous and sustainable learning, the boredom of students, development of learners’ technological skills, acquiring informal skills, fast feedback, and reducing the quality of education (6 components and 41 open codes); the personality concepts included increasing individual-educational efficiency, increasing psychological-social problems, addiction to cyberspace, changes in the student’s social perspective (4 components and 33 open codes); the cultural concepts included changes in the thought pattern, social interactions and lifestyle, fashionism, moral deviation, and development of interpersonal communication (6 components and 33 open codes); and the belief concepts included ambivalence, access to inappropriate content, better understanding of religious facts, tendency to deviant thoughts, and acceptance of opposing patterns (5 components and 24 open codes).Conclusion: The research findings show that despite some unfavorable outcomes, the positive ones stand out and highlight the significance of parental and school supervision, as it can help students follow this path with the most excellent effectiveness and the slightest vulnerability.